Gastrodia fujianensis (Orchidaceae, Epidendroideae, Gastrodieae), a new species from China - Ma, Liang; Chen, Xin-Yan; Liu, Jiang-Feng; Chen, Shi-Pin (Phytotaxa, 2019)
Gastrodia Brown (1810: 330) (Orchidaceae, Epidendroideae, Gastrodieae) is composed of approximately 90 species with a broad Old World distribution (Pridgeon et al. 2005, Chen et al. 2009, Cribb et al. 2010, Huang et al. 2015, Hsu et al. 2016, Jin et al. 2017, Aung et al. 2018, Suetsugu 2017, Suetsugu et al. 2018). During a survey of native plants in Fujian Province, an unknown species of Gastrodia was collected in August 2018 from the evergreen broad-leaved forest in Wuyishan National Park. A detailed examination of the specimens with similar species morphologically, G. fontinalis Lin (1987: 129), G. major Averyanov (2006: 21), G. punctata Averyanov (2006: 21) and G. huapingensis Huang, Hu & Liu (2015: 290), and two other species recorded from Fujian, G. elata Blume (1856: 174) and G. wuyishanensis Li & Liu (2007: 354), we confirmed it as a new species.